Analisis Lingkungan Kerja Menggunakan Metode 5S dan Diagram Pie pada Gudang 03 Electrical Divisi Supply Chain PT. XYZ - Nanda Setyadi; Dira Ernawati (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Until now, many warehouses in companies are still not neatly arranged, this is because the storage layout is not perfect, making it difficult for employees to reach the materials that will be taken for use in production activities. PT. XYZ is the largest shipbuilding company in Indonesia. PT XYZ also has several warehouses, one of which is Warehouse 03 electrical. This research aims to help optimize the efficiency level of Warehouse 03 Electrical PT. XYZ uses the 5S method and Pie Chart. The implementation of the 5S culture in Warehouse 03 electrical is implemented according to the applicable SOP, but the implementation is not yet optimal. Application of the 5S method in warehouse 03 electrical PT. XYZ It is felt that XYZ is not yet optimal because only 2S (Seiso and Seiketsu) is running optimally. while 3S (Seiri, Seiton, Shitsuke) has not run optimally. Therefore, this research was conducted to evaluate the application of the 5S method in the 03 electrical warehouse of PT. XYZ. The evaluation results using the 5S method and Pie Diagram aim to support and increase productivity in the Warehouse 03 electrical area as well as company performance